Pengetahuan dan Sistem Pengelolaan Pertambangan Minyak Rakyat di Gampong Alue Dua Aceh Timur - Fitriani; Ade Ikhsan Kamil (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
This article discusses the knowledge of community oil miners in the People's Mining in Alue Dua Village, Rantau Peureulak District, East Aceh Regency. The author collects data using participatory observation, in-depth interviews and corroborates it by studying literature. The results showed that the knowledge of miners in Gampong Alue Dua was formed along with the history of the emergence of mining in Peureulak, especially when the oil companies entered to take samples of land as proof that the Peureulak area has the potential to contain oil, and also because of self-taught learning. For miners, there are 4 special signs in identifying land that has the potential to contain oil: 1) the land selected for drilling that is close to and is still in the same lane as the Dutch heritage lake. 2) The distance between the land which is the drilling position and the Dutch heritage lake is about 100-150 meters. 3) Selection of old wells or Dutch heritage ponds with the category of no longer active. 4) Get back to the miners' technicians at work.